Distinctive Signaling Profiles With Distinct Biological and Clinical Implications in Aggressive CLL Subsets With Stereotyped B-Cell Receptor Immunoglobulin - Gerousi, Marina; Laidou, Stamatia; Gemenetzi, Katerina; Stamatopoulos, Kostas; Chatzidimitriou, Anastasia (Frontiers in Oncology, 2021)
The ontogeny and evolution of chronic lymphocytic leukemia (CLL) are critically dependent on interactions between leukemic cells and their microenvironment, including antigens, the latter recognized through the clonotypic B-cell receptor immunoglobulin (BcR IG). Antigen selection is key to the pathogenesis of CLL, as evidenced by the remarkable skewing of the BcR IG gene repertoire, culminating in BcR IG stereotypy, referring to the existence of subsets of patients with (quasi)identical BcR IG. Notably, certain of these subsets have been found to display distinct, subset-biased biological background, clinical presentation, and outcome, including the response to treatment. This points to BcR IG centrality while also emphasizing the need to dissect the signaling pathways triggered by the distinctive BcR IG expressed by different subsets, particularly those with aggressive clinical behavior. In this mini-review, we discuss the current knowledge on the implicated signaling pathways as well as the recurrent gene mutations in these pathways that characterize major aggressive stereotyped subsets. Special emphasis is given on the intertwining of BcR IG and Toll-like receptor (TLR) signaling and the molecular characterization of signaling activation, which has revealed novel players implicated in shaping clinical aggressiveness in CLL, e.g., the histone methyltransferase EZH2 and the transcription factor p63.